2019
DOI: 10.1155/2019/9237181
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and Determinants of Prescribing for Parkinson’s Disease: A Systematic Literature Review

Abstract: Since the discovery of levodopa (L-dopa) in 1967, the range of medications available to treat Parkinson's disease has increased significantly and guidance on the use, efficacy, and safety of these medications has evolved. To assess levels of adherence to national prescribing guidelines and awareness of changes in the efficacy and safety data published in the profiles of medications for the treatment of PD, we have reviewed studies on patterns and determinants of prescribing PD medications conducted in the last… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 141 publications
(690 reference statements)
1
23
0
1
Order By: Relevance
“…Specifically, since PD has been ascertained to be age-dependent [ 3 ], the increasing treatment incidence with age was expected. Moreover, the selegiline cohort was the oldest, in line with literature [ 4 , 7 ]. The high prevalence of comorbidities was also foreseen, due to the older age of the cohorts and the high risk for multimorbidity in patients affected by PD [ 26 ], such as cardiovascular, musculoskeletal, and mental disorders, which in turn increases the need for support, morbidity, and mortality.…”
Section: Discussionsupporting
confidence: 80%
“…Specifically, since PD has been ascertained to be age-dependent [ 3 ], the increasing treatment incidence with age was expected. Moreover, the selegiline cohort was the oldest, in line with literature [ 4 , 7 ]. The high prevalence of comorbidities was also foreseen, due to the older age of the cohorts and the high risk for multimorbidity in patients affected by PD [ 26 ], such as cardiovascular, musculoskeletal, and mental disorders, which in turn increases the need for support, morbidity, and mortality.…”
Section: Discussionsupporting
confidence: 80%
“…In another study, conducted in the United Kingdom between 2004 and 2015, 21% of over 6000 people with PD treated with anti-PD medication were taking ropinirole monotherapy and a further 17% were taking pergolide monotherapy, over a median follow-up duration of 2.8 years [27]. The lower use of dopamine agonist monotherapy in PRISM may reflect changes in treatment recommendations and prescribing practice over time, since dopamine agonists and MAO-B inhibitors were preferred over levodopa as initial monotherapy options 25 years ago because of their perceived potential to delay the onset of dyskinesia and/or motor fluctuations, and a misplaced notion that they were neuroprotective [28].…”
Section: Discussionmentioning
confidence: 99%
“…Safinamide has other effects beneficial against PD including blockage of voltage-dependent sodium channels and has low tyramine potentiation [164]. When reversible and irreversible inhibitors are compared, both have been found to be effective as adjuvant therapy to delay or reduce the need for Ldopa [165]. However, a meta-analysis comparing MAOI alone or with L-dopa showed that selegiline was the most effective drug and that both it and rasagiline were more effective than safinamide (selegiline > rasagiline > safinamide) [166].…”
Section: The Pharma Debate-reversible or Irreversible Inhibition?mentioning
confidence: 99%
“…This is partly due to the side effects that require dietary restrictions but probably more due to inexperience with these drugs [167,168]. Certainly for Parkinson's disease, prescribing habits vary from country to country [165].…”
Section: The Pharma Debate-reversible or Irreversible Inhibition?mentioning
confidence: 99%